Proteomic Profiling of Bifidobacterium bifidum S17 Cultivated Under In Vitro Conditions - Wei, Xiao; Wang, Simiao; Zhao, Xiangna; Wang, Xuesong; Li, Huan; Lin, Weishi; Lu, Jing; Zhurina, Daria; Li, Boxing; Riedel, Christian U.; Sun, Yansong; Yuan, Jing (Frontiers in Microbiology, 2016)
Bifidobacteria are frequently used in probiotic food and dairy products. Bifidobacterium bifidum S17 is a promising probiotic candidate strain that displays strong adhesion to intestinal epithelial cells and elicits potent anti-inflammatory capacity both in vitro and in murine models of colitis. The recently sequenced genome of B. bifidum S17 has a size of about 2.2 Mb and encodes 1,782 predicted protein-coding genes. In the present study, a comprehensive proteomic profiling was carried out to identify and characterize proteins expressed by B. bifidum S17. A total of 1148 proteins entries were identified by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS), representing 64.4% of the predicted proteome. 719 proteins could be assigned to functional categories according to cluster of orthologous groups of proteins (COGs). The COG distribution of the detected proteins highly correlates with that of the complete predicted proteome suggesting a good coverage and representation of the genomic content of B. bifidum S17 by the proteome. COGs that were highly present in the proteome of B. bifidum S17 were Translation, Amino Acid Transport and Metabolism, and Carbohydrate Transport and Metabolism. Complete sets of enzymes for both the bifidus shunt and the Embden-Meyerhof pathway were identified. Further bioinformatic analysis yielded 28 proteins with a predicted extracellular localization including 14 proteins with an LPxTG-motif for cell wall anchoring and two proteins (elongation factor Tu and enolase) with a potential moonlighting function in adhesion. Amongst the predicted extracellular proteins were five of six pilin proteins encoded in the B. bifidum S17 genome as well as several other proteins with a potential role in interaction with host structures. The presented results are the first compilation of a proteomic reference profile for a B. bifidum strain and will facilitate analysis of the molecular mechanisms of physiology, host-interactions and beneficial effects of a potential probiotic strain.